1997
DOI: 10.1055/s-2007-973695
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Central Motor Reorganization in Pediatric Hemiplegic Patients

Abstract: Twenty hemiplegic patients were studied with transcranial magnetic stimulation (TMS). Motor evoked potentials (MEPs) of the biceps brachii (BB) and the abductor pollicis brevis muscles (APB) were recorded on both sides simultaneously. TMS was carried out with an 8-shaped coil over different scalp positions in the intact hemisphere. Bilateral MEPs of BB were elicited in patients with later childhood lesions as well as early lesion, but those of APB were only elicited in the latter (up to 2 years). In patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(43 citation statements)
references
References 1 publication
2
39
0
2
Order By: Relevance
“…18 In children with congenital hemiplegia, ipsilateral connections are enhanced. 19,20 In adults with chronic stroke, their relative role is unclear although they have been associated with worse motor outcome. 21 Detection of ipsilateral pathways using functional MRI or transcranial magnetic stimulation could validate this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…18 In children with congenital hemiplegia, ipsilateral connections are enhanced. 19,20 In adults with chronic stroke, their relative role is unclear although they have been associated with worse motor outcome. 21 Detection of ipsilateral pathways using functional MRI or transcranial magnetic stimulation could validate this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…We propose that the more limited distal muscle motor control in older hemispherectomy subjects probably involves other subcortical mechanisms such as the cortico-reticulospinal and propriospinal inputs to the spinal cord that are less efficient than corticospinal tracts. 39 On the basis of this anatomical information, one might expect voluntary ankle dorsiflexion of each foot to be accompanied by activation within overlapping portions of S1M1, as well as adaptations induced by skills learning, such as representational expansion or increased overlap during movement of the paretic and nonparetic ankle in patients with a younger age at surgery/ injury. Our study seems to have revealed such changes.…”
Section: Discussionmentioning
confidence: 99%
“…Eventually, the contralesional hemisphere can become equipped with fast-conducting ipsilateral projections to the paretic extremities (Eyre et al 2001;Staudt et al 2002a). This type of cortico-spinal (re)organization can occur throughout the pre-and perinatal period (Staudt et al 2004), during the first months of life (Eyre et al 2007) and, in one case report, even up to the age of 2 years (Maegaki et al 1997). In children beyond this age and in adult stroke patients, such fast-conducting projections have, to date, never been reported.…”
Section: Reorganization In the Motor Systemmentioning
confidence: 95%